Effects of sleep on human psychology and psychological health - Rustamjonov Lazizbek (Euro Asian Journal Publishing, 2024)
This article describes the effects of sleep on human psychology and mental and biological health as much as possible after 22:00 p.m. The mechanism outlines thoughts that sleeping is a factor that ensures that it is psychologically healthy for the next day.
Keywords: Sleep; psychology; memory; hormones